How Do Virtual Visits Compare? Parent Satisfaction With Pediatric Diabetes Telehealth During the COVID-19 Pandemic - March, Christine A.; Muzumdar, Radhika; Libman, Ingrid (Frontiers in Clinical Diabetes and Healthcare, 2022)
Background In response to the COVID-19 pandemic, many countries relaxed restrictions on telemedicine, allowing for a robust transition to virtual visits for routine care. In response, centers rapidly instituted and scaled telemedicine for pediatric diabetes care. Despite numerous center reports on their experience, little is known about parent perspectives on the widespread increase of telemedicine for pediatric diabetes appointments. Objective To assess parent satisfaction with virtual care for pediatric diabetes during the COVID-19 pandemic. Methods We conducted an online, cross-sectional survey of parents of youth with diabetes who receive care at a large, academic diabetes center regarding their perspectives on newly introduced virtual appointments. Parents were surveyed at two time points during the pandemic using a validated scale which was adapted for diabetes. We explored demographic and clinical factors which may influence parental satisfaction. Results Overall, parents expressed high levels of satisfaction (>90%) with functional aspects of the visit, though only approximately half (56%) felt the visit was as good as an in-person encounter. Nearly three-quarters (74%) would consider using telemedicine again in the future. Prior use of telemedicine significantly influenced parent satisfaction, suggesting that parent preferences may play a role in continued use of telemedicine in the future. There was no difference in responses across the two timepoints, suggesting high satisfaction early in the pandemic which persisted. Conclusions If permissive policies for telemedicine continue, diabetes centers could adopt hybrid in-person and virtual care models, while considering various stakeholder perspectives (providers and patients) and equity in access to virtual care.